Interplay between FOXO, TOR, and Akt - Hay, Nissim (2011)
FOXO transcription factors have emerged as rheostats that coordinate the activities of Akt and target of rapamycin complexes (TORCs). This review summarizes the regulatory circuits mediated by the activation of FOXO, which in turn modulate Akt and TORCs activities. The biological significance of these regulatory circuits is discussed in this article.